Analisis Pesan Moral Pada Film Bayi Ajaib Tahun 2023 - Nurvitasari, Tri; Hamidah; Hamandia, Muhammad Randicha (Pubmedia Social Sciences and Humanities, 2024)
Mass communication broadly is an activity carried out between one or more people to convey messages through print, electronic or digital mass media with the expectation of reciprocity. One of the media used to convey messages is film. Film is a mass media that is considered effective in conveying messages compared to other communication media. Film is a new means used to disseminate entertainment that has become a previous habit, as well as presenting stories, events, music, drama, comedy and other technical presentations to the general public. Films not only serve entertainment functions, but also contain informative, educative and even persuasive functions. In the current era, there are many types of films that educate film lovers, especially in Indonesia. There are various types of films including drama, romance, comedy, action and horror, such as the film Miracle Baby 2023. The film Miracle Baby 2023 is one of the Indonesian horror films which will be shown in Indonesian cinemas in January 2023, which tells the story of two young people. -sama wants to become rich, but in the wrong way. This magical baby film also contains many moral messages. Moral messages are statements that convey instructions, regulations, or invitations regarding societal conventions, morality, and culture so that humans can live better and as material for self-evaluation in actions. The moral messages contained in the 2023 Magic Baby Film are: 1) moral messages in the category of human relationships with God , 2) moral messages in the category of human relationships messages in the category of human relationships with themselves, and 3) moral messages in the category of human relationships with other humans.